Inclusión de estudiantes con necesidades educativas especiales en el aula regular (2018)
The purpose of this research was to analyse the functional dynamics of the inclusion process of students with special educational needs within the regular classroom. The research was based on a mixed approach of a descriptive nature. The population and sample were forty (40) students in the fourth and fifth grade of primary school, forty (40) teachers and directors and forty (40) parents, focused in four (4) educational institutions of the department two of them official belonging to the rural area of the island and the other two private located in the urban area. A questionnaire was used as instrument to obtain required information. The questionnaires were validated by three (03) experts and subjected to the Lickert scale to obtain reliability. After the processing of the results, it is established that the educational community (teachers, managers, parents) requires more training in terms of educational inclusion and institutions must improve not only physical but technological infrastructure for the improvement of the quality, access and permanence of students with special educational needs. Finally, it was concluded that the conditions of sustainability, processes and resources are scarce or non-existent for the inclusion processes in the educational institutions. It is evident the lack of preparation of teachers in the topic of inclusion and in methodological strategies for the construction and application of an adequate curriculum in the classroom, and also that it entails to contemplate in the curricular approach, aspects of the ethnic territory.